103k views
19 votes
Expand quadratic equation (2x-3)(x+4) = 0​

2 Answers

2 votes

Answer:

Explanation:

Simplifying

(2x + -3)(x + -4) = 0

Reorder the terms:

(-3 + 2x)(x + -4) = 0

Reorder the terms:

(-3 + 2x)(-4 + x) = 0

Multiply (-3 + 2x) * (-4 + x)

(-3(-4 + x) + 2x * (-4 + x)) = 0

((-4 * -3 + x * -3) + 2x * (-4 + x)) = 0

((12 + -3x) + 2x * (-4 + x)) = 0

(12 + -3x + (-4 * 2x + x * 2x)) = 0

(12 + -3x + (-8x + 2x2)) = 0

Combine like terms: -3x + -8x = -11x

(12 + -11x + 2x2) = 0

Solving

12 + -11x + 2x2 = 0

Solving for variable 'x'.

Factor a trinomial.

(3 + -2x)(4 + -1x) = 0

Subproblem 1

Set the factor '(3 + -2x)' equal to zero and attempt to solve:

Simplifying

3 + -2x = 0

Solving

3 + -2x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.

3 + -3 + -2x = 0 + -3

Combine like terms: 3 + -3 = 0

0 + -2x = 0 + -3

-2x = 0 + -3

Combine like terms: 0 + -3 = -3

-2x = -3

Divide each side by '-2'.

x = 1.5

Simplifying

x = 1.5

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve:

Simplifying

4 + -1x = 0

Solving

4 + -1x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.

4 + -4 + -1x = 0 + -4

Combine like terms: 4 + -4 = 0

0 + -1x = 0 + -4

-1x = 0 + -4

Combine like terms: 0 + -4 = -4

-1x = -4

Divide each side by '-1'.

x = 4

Simplifying

x = 4

Solution

x = {1.5, 4}

User Yui
by
4.6k points
8 votes

Answer:


2x^2+5x-12=0

Explanation:

Algebra

To expand the given equation


(2x-3)(x+4)=0

we'll use the distributive property by multiplying each term of the first binomial by each term of the second binomial as follows:


2x^2+8x-3x-12=0

Rearranging and simplifying:


\mathbf{2x^2+5x-12=0}

User RodrikTheReader
by
4.7k points